Do government tools influence organizational performance? Examining their implementation in early childhood education - Sandfort, Jodi; Sowa, Jessica E.; Selden, Sally Coleman (2008)
This article explores whether the multiple tools used by government to implement social policy influence organizational performance. This analysis focuses on three tools - grants, contracts, and vouchers - and their use in the field of early childhood care and education. Through analysis of a field-based study of 22 organizations, the authors explore qualitative evidence and examine the relative consequences of each tool using multivariate modeling. the authors conceptualize organizational performance along four dimensions - management capacity, management outcomes, program capacity, and program outcomes - to better explore how government tools influence organizations delivering publicly funded services. Findings reveal that the different tools the government uses to implement early childhood programs have distinct consequences; grants have the most significant, positive consequences on a variety of desirable outcomes. - Reproduced.
Keywords: Early childhood education; Performance appraisal; Public administration